Christian Education and the Shifting Farm: The Existential Sustainability of the Dayak Ma’anyan Cultural Heritage - Munte, Alfonso (Institut Agama Kristen Negeri Toraja, 2025)
This research explores the experiences, narratives, and policies of the Menugal culture within the Dayak Ma’anyan community in Lenggang Village, Kalimantan Tengah, with particular focus on its connection to Christian education. The study examines how traditional practices of cultivating mountain rice varieties relate to Christianity, interfaith encounters, cultural preservation, and sustainable agricultural values amid the global food crisis. A qualitative approach was used, including in-depth interviews with Damang (Pangulu Adat), Mantir Adat, and three informants (Tochyhat, Dkakhgma, and Gkedhy), supported by audio recordings and photographic documentation. Drawing on perspectives from cultural preservation and Christian education, the analysis demonstrates that indigenous agricultural practices serve as pedagogical spaces in which values of patience, stewardship, and communal responsibility are passed down through generations. The findings show that villagers’ livelihood strategies are strengthened by traditional land cultivation and post-harvest techniques that resist fast, industrialized methods, while promoting resilience and ecological awareness. These practices align with Christian educational frameworks that emphasize moral development, interfaith respect, and care for creation. In this way, the Menugal tradition contributes not only to food security but also to local Christian education that integrates faith, culture, and sustainability.